Transformasi Olahraga Daerah: Implementasi Mata Kuliah PHS (Perilaku Hidup Sehat) Dalam Penerapan Tanaman Obat Keluarga Di SMP Negeri 8 Gorontalo - Paisal, Rifcha; Haryani, Meri; Irawan, Safri; Hadia, Moh Hendrik; Sahbudin, Mohamad Darmawan; Malengga, Ruslin; Abu, Ahmad H.; Butolo, Mohammad Fadhil; Kasim, Faisal; Kasim, Ariyanto; Umar, Sriwahyuni; Datukramat, Gina Riskita (Universitas Negeri Gorontalo, 2025)
The socialization and practical planting of Family Medicinal Plants (TOGA) at SMP Negeri 8 Gorontalo aimed to introduce the importance of utilizing medicinal plants as a healthy and natural alternative for treatment. This program was carried out as part of the implementation of the Healthy Living Behavior (PHS) course and involved 25 students from grade VIII. The activities began with administrative preparations, including the creation of permission letters and coordination with the school. The socialization of TOGA included a presentation on the benefits and usage of medicinal plants, followed by a hands-on planting session in the schoolyard. The results showed high enthusiasm from the students, evident from their active participation during the presentation and the practical planting session. It is expected that this activity will increase students' knowledge about the importance of living a healthy life and utilizing local natural resources for minor health treatments. This program is also expected to raise awareness about self-reliance in maintaining health through the use of family medicinal plants in the home environment.